Floods Trajectories Modeling and Dynamic Relief Planning: A Bees Foraging Approach - Hmaidi, Kawther; Akaichi, Jalel (Swarm Intelligence Based Optimization, 2014)
Natural disasters represent hazards resulting from extreme geophysical events. Floods particularly are one of the most occurring disasters. They affect annually different regions of the world with varying intensities causing materiel damages and fatalities. Despite the efforts done by rescue agents in this context, inefficiencies occur yet. Thus, the need of disaster management information systems is becoming critical to mitigate the effect of natural hazards. In this paper, we aim to provide a dynamic decision making tool inspired by the foraging behavior of honey bees which assists in managing relief operations and assigning rescue agents to affected areas. We propose, equally, a trajectory data warehouse model for flood tracking and affected areas location.